Idosos na EJA: contribuições a partir do periódico Psicologia: reflexão e crítica (de 2000 a 2012) - Costa, Adriana Zakia (Universidade Federal de São Carlos, 2014)
According to the Brazilian Institute of Geography and Statistics (IBGE), population aging integrates our current context and occurs extensively in Brazil, which makes it worth considering by public social policies. On this account, it is important to understand that aging is a heterogeneous process marked by losses and gains as some of our cognitive functions tend to decline while others remain and are enhanced over time, especially those connected with cultural stimuli. In this sense, education towards the elderly is of great importance and it must be conceived from continuing education, linked to the concept of lifelong education. As the Youth and Adult Education (EJA) is one of the actions promoted by lifelong education as well as one of the educational spaces having the presence of the elderly, it is important to understand who they are, the ones integrating this type of basic education, in order to provide them with appropriate service regarding their specificities and interests so that their right to quality education is guaranteed as it is established by the national legislation. This research was based on the analysis of articles of the Brazilian journal of Psychology - Psychology: Reflection and critique - in order to identify elements that can collaborate with the service provided to the elderly while subjects composing the EJA. Therefore, a bibliographical research was carried out in which 40 articles of the journal in question were selected, between the years 2000-2012, having the following keywords as the criteria: aging, old age, the elderly, elderly men, elderly women. To perform the analysis of the articles the technique of content analysis was employed. From the analysis of the articles it was possible to organize nine elements that contribute to the reflection and action towards the service provided to the elderly in the EJA: 1) meet the specificities, needs and interests of the elderly seeking the EJA, thus understanding the heterogeneity of aging; 2) understand that the cognition of the elderly involves gains and losses and a favorable cultural environment can offset losses and promote cognitive gains; 3) stimulate the high sense of self-efficacy of these elderly subjects; 4) understand that the processes of teaching and learning can be enhanced with the collective environment of intergenerational interaction of the EJA; 5) seek to overcome stereotypes, prejudices and negative beliefs about old age; 6) understand that the tools and knowledge provided by schooling are relevant to the autonomy, citizenship and social inclusion of the elderly in the present society; 7) value the knowledge and life experience that the elderly carry; 8) provide educational materials which are adequate for the reductions of some sensory abilities, such as vision and hearing; 9) conceive the perspective of development throughout life (life-span). In this sense, we suggest the social and academic relevance of the theme of the elderly in the EJA and the furtherance of new studies and research in order to increase scientific production in education and consolidate the knowledge about the educational practice for this population.
Keywords: Educação de jovens e adultos; Sujeitos da EJA; Idosos; Youth and adult education; EJA individuals; The elderly; CIENCIAS HUMANAS::EDUCACAO